Synthesis, Antimalarial, Antileishmanial, and Cytotoxicity Activities and Preliminary In Silico ADMET Studies of 2-(7-Chloroquinolin-4-ylamino)ethyl Benzoate Derivatives - Gutiérrez, Joyce E; Ramírez, Hegira; Fernandez-Moreira, Esteban; Acosta, María E; Mijares, Michael R; De Sanctis, Juan Bautista; Gurská, Soňa; Džubák, Petr; Hajdúch, Marián; Labrador-Fagúndez, Liesangerli; Stella, Bruno G; Díaz-Pérez, Luis José; et al. (Pharmaceuticals (Basel, Switzerland), 2023)
A series of heterocyclic chloroquine hybrids, containing a chain of two carbon atoms at position four of the quinolinic chain and acting as a link between quinoline and several benzoyl groups, is synthesized and screened in vitro as an inhibitor of β-hematin formation and in vivo for its antimalarial activity against chloroquine-sensitive strains of Plasmodium berghei ANKA in this study. The compounds significantly reduced haeme crystallization, with IC50 values < 10 µM. The values were comparable to chloroquine's, with an IC50 of 1.50 ± 0.01 µM. The compounds 4c and 4e prolonged the average survival time of the infected mice to 16.7 ± 2.16 and 14.4 ± 1.20 days, respectively. We also studied the effect of the compounds 4b, 4c, and 4e on another important human parasite, Leishmania mexicana, which is responsible for cutaneous leishmaniasis, demonstrating a potential leishmanicidal effect against promasigotes, with an IC50 < 10 µM. Concerning the possible mechanism of action of these compounds on Lesihmania mexicana, we performed experiments demonstrating that these three compounds could induce the collapse of the parasite mitochondrial electrochemical membrane potential (Δφ). The in vitro cytotoxicity assays against mammalian cancerous and noncancerous human cell lines showed that the studied compounds exhibit low cytotoxic effects. The ADME/Tox analysis predicted moderate lipophilicity values, low unbound fraction values, and a poor distribution for these compounds. Therefore, moderate bioavailability was expected. We calculated other molecular descriptors, such as the topological polar surface area, according to Veber's rules, and except for 2 and 4i, the rest of the compounds violated this descriptor, demonstrating the low antimalarial activity of our compounds in vivo.
Keywords: malaria; aminoalkylbenzoates; cytotoxicity; leishmaniasis; chloroquine; ADMET